TRAVELOGUE-FRAGMENTS OF IVO ANDRIĆ - Zvjezdana Radoš (Hum, 2012)
This work, from a position of poetics and imagology, analyzes travel prose of Ivo Andrić, mainly collected in the book Staze, lica, predeli / Runs, faces, landscapes (1963, enlarged edition 1981), and published in periodicals since 1914 to mid-sixties of the last century. The poetic and meditative component of Andrić’s travelogues and their pronounced fragmentation are especially under consideration. On the other hand, attention is directed toward the documentary-publishing and political- pragmatic dimension of that prose; toward self-images and heteroimages in it, too. Stylistic and poetic intimacy between Andrić’s travelogues and his youthful lyric-reflective prose and later Znakovi pored puta / Sings along the road is observed on the basis of such considerations, including his creativity in general, while analysis of self-images and hetero- images places his travel prose into the biographical context.